REVIEW: PRODUKSI LIMONENE MELALUI REKAYASA JALUR PENTOSA FOSFAT MENGGUNAKAN CYANOBACTERIUM Synechocystis sp. PCC 6803 - Azar, Alda Wydia Prihartini; Hasna Dyah Kusumardani; Haris Maulani (Jurnal Biogenerasi, 2025)
Limonene, a terpenoid compound found in various plants such as oranges, lemons, and mint, has numerous applications in different industrial fields, including as a fragrance, flavoring agent, and biofuel. Conventional limonene production relies on agricultural outputs vulnerable to fluctuations caused by diseases or climate change. Therefore, metabolic engineering using microorganisms offers an interesting alternative for more efficient and sustainable limonene production. This review article aims to summarize the procedures for limonene production through the modification of the pentose phosphate (PP) and methylerythritol 4-phosphate (MEP) biosynthetic pathways in the cyanobacterium Synechocystis sp. PCC 6803 to produce limonene. Limonene synthase (lims) obtained from C. limon and M. spicata plants was cloned and transformed into cyanobacteria to enhance limonene production. Experimental results showed that genes associated with the limonene biosynthesis pathway, including ribose 5-phosphate isomerase (rpi), ribulose 5-phosphate 3-epimerase (rpe), and geranyl diphosphate synthase (gpps), were successfully expressed in Synechocystis. This study demonstrates that Synechocystis can be an efficient microbial system for limonene and other isoprene compound production, offering a more stable and environmentally friendly alternative than agricultural-based production.